Treatment of platelet concentrates with ultraviolet C light for pathogen reduction increases cytokine accumulation. Issue 6 (15th April 2016) - Sandgren, Per; Berlin, Gösta; Tynngård, Nahreen
Abstract : BACKGROUND: Pathogen reduction technologies use photoactive substances in combination with ultraviolet (UV) light to inactivate pathogens. A new method uses only UVC light for pathogen reduction. This study assesses the effects of UVC light treatment on cytokine release in platelet (PLT) concentrates (PCs). STUDY DESIGN AND METHODS: A PC with 35% plasma and 65% PLT additive solution (SSP+) was prepared from five buffy coats. Three such PCs were pooled and divided into 3 units. One unit was used as a nonirradiated control, the second was a gamma‐irradiated control, and the third unit was treated with UVC light technology. Ten units of each type were investigated. Cytokine release was analyzed on Days 1, 5, and 7 of storage. Correlation between cytokines, PLT surface markers, and hemostatic properties was investigated. RESULTS: Swirling was well preserved and pH was above the reference limit of 6.4 during storage of PLTs in all groups. Cytokine levels increased during storage in all groups but to a larger degree in PCs treated with UVC light. Only weak correlation was found between cytokines and PLT surface markers (r < 0.5). However, several cytokines showed strong correlation (r > 0.6) with the PLTs' ability to promote clot retraction. CONCLUSION: UVC treatment resulted in increased release from PLT alpha granules as evident by a higher cytokine release compared to nonirradiated and gamma‐irradiated PCs. The clinical relevance of these findings needs to be further evaluated.